142 Onset of preeclampsia is preceded by structural capillary rarefaction. (16th May 2012) - Nama, V; Manyonda, I T; Onwude, J; Antonios, T F T
Abstract : Introduction: Microvascular rarefaction, defined as reduced vascular density, is a consistent finding in hypertension. Functional and structural capillary rarefaction occurs in individuals with sustained and borderline essential hypertension, and in their normotensive offspring. Women who develop preeclampsia are at increased risk of hypertension in later life. We hypothesised that capillary rarefaction precedes the onset of preeclampsia and could play a role in its pathogenesis. Methods: In this longitudinal cohort study we recruited 322 Caucasian women, of which 305 subjects completed the study. We used intravital video-microscopy to measure basal (ie, functional) and maximal (ie, structural) skin capillary densities according to a well-validated protocol and measured plasma angiogenic and anti-angiogenic factors. Subjects were studied at five consecutive visits. Results: Preeclampsia occurred in 16 women (mean onset at 35.6±4.8 weeks) and 272 women had normal pregnancy. In women with normal pregnancy significant structural reduction in capillary density occurred at 27–32 weeks, which had resolved by the puerperium (mean change: −2.2 capillaries/field, 95% CI −3.6 to −0.7). In contrast, in women who developed preeclampsia, more significant structural rarefaction was observed earlier at 20–24 weeks (mean change: −6.1 capillaries/field, 95% CI −9.2 to −2.9), which persisted into the puerperium. We also found that the change in soluble Endoglin from 11–16 weeks to 27–32 weeks was significantly correlated with the change in structural capillary density. Conclusions: This is the first study to show that significant structural capillary rarefaction precedes the onset of preeclampsia. Capillary rarefaction could play a role in the pathogenesis of this disease.